APPLICATION OF COMPLEX OF GEOPHYSICAL METHODS TO RISE PROGNOSIS RELIABILITY OF OIL AND GAS DEPOSITS IS THE NORTHERN SIDE OF DNIEPER- DONETSK DEPRESSION - SOROKIN, O.; SLOBODIANIUK, S.; SIRCHENKO, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2006)
Authenticity prediction of hydrocarbons deposit, at the searches and exploring of hydrocarbons reservoirs by geophysical methods, relies on informing of every method in concrete geological condition and is characterized by the factor of definiteness 0